Experiment Study: Auditor’s Going Concern Opinion Decision During Covid 19 Pandemic - Rr. Puruwita Wardani; Susanna Hartanto (International Journal of Organizational Behavior and Policy, 2023)
This research is an experimental research that assesses the giving of going concern opinions conducted by auditors during the Covid 19 pandemic. To enhance the degree of confidence in the financial statements, a qualified external party (an auditor) is engaged to examine the financial statements. However, Auditors are increasingly being asked to provide assurance on non-financial information, both on a standalone basis or in conjunction with the audit of normal financial statements. Auditors shall perform a risk assessment in order for continuity of the going concernThe participants who participated and can be used in this study are members of IAPI in the East Java region as many as 40 auditor. Participants in this research have experiences in positions as senior auditors, supervisors, managers and partners. The results of this study are that auditors do not differentiate in auditing the functioning and non-functioning companies in the context of giving going-concern opinion decisions. Auditor considers financial information more than non-financial information in giving a going concern opinion because financial information is historical data that can be used to assess the company's current condition and to predict future financial conditions. Non-financial information is used as supporting information for going concern decision making.